Traditional African vegetables: Directory of research and development specialists - Koeijer, H. de; hweya, J.A.; Attere, A.F. (1999)
The main function of this directory lies in the usefulness of the information it conveys. It has a record of contact information drawn from an IPGRI database of traditional vegetable workers, institutions and networks in sub-Saharan Africa. An international community of experts and workers in the area of ”Traditional African Vegetables” already exists and is engaged in productive research and dialogue. With the presentation of this first edition of the directory of ”Traditional African Vegetable Workers” we look forward to enabling direct contacts between these researchers and workers on all aspects of traditional African vegetables. The scope of the directory is to give information on who works on African vegetables in the region and to provide a vehicle for fostering links between the workers. We would like to create an environment where information is exchanged easily between researchers and workers. The challenge is that the role and the potential of information and information exchange, and the sharing of experiences is becoming much more important in the face of growing threat of genetic erosion to our traditional African vegetable resources. The workers listed in this directory have responded to the challenge by ensuring conservation and continued use of the genetic resources of traditional African vegetables through their research, and we laud their efforts.